PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, RELIGIUSITAS, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI - Mahmud; Wati, Erlina Kartini; Subhan, Ega Saiful; Irwansyah (Universitas Nusantara PGRI Kediri, 2024)
Repairing government employee performance is one of the important issues in public administration reform in various countries. This study was conducted to find out what things can affect employee performance. In this study, how does the influence of transformational leadership style, religiosity and physical work environment on employee performance at the Dompu Regency Industry and Trade Service Descriptive quantitative research sample of 32 employees with saturated sampling techniques. Data collection techniques are observation and questionnaire methods. SEM-PLS v 3 data analysis technique. Transformational leadership style (X1) does not affect employee performance, religiosity (X2) does not partially affect performance, and the physical work environment (X3) has a significant effect on employee performance (Y). The contribution of this study can improve employee performance efforts through the variables that influence it.